Use of Reference Management Software by Graduate Students: A Case Study at Gadjah Mada University, Indonesia - Purwani Istiana; Shivendra Singh (Department Library of Governance Institut of Home Affairs, 2025)
Abstract Problem Statement: Large-scale analysis at Gadjah Mada University (UGM), Indonesia, to assess students’ awareness and usage of Reference Management Software (RMS) in academic writing tools has been limited. Purpose: This study aimed to examine the extent to which postgraduate students at UGM are familiar with and use RMS in analysis and academic writing. Method: A descriptive survey method was applied using an online questionnaire distributed to postgraduate students at Faculty of Geography, UGM. Furthermore, a total of 52 valid responses were collected and analyzed. Results: The results showed that 94.2% (49) of students were aware of RMS, such as Mendeley, Zotero, and EndNote. The remaining 5.8% (3) were not aware of the existence of RMS. Mendeley was the most widely used, and out of the 49 students who were aware of the existence of RMS, only 2% or 1, did not adopt the application in scientific writing. The knowledge of the software was obtained from librarians or libraries in 44% of cases. Conclusion: Librarians play an important role in enhancing students’ ability to use RMS effectively. This study recommends that libraries continue to offer structured and periodic training programs to strengthen students’ productivity and digital literacy. The results contribute new insights into RMS adoption in Indonesian higher education and report the evolving role of librarians in supporting activities.